POTHIER, THE STRAYING MULE AND THE UNRULY BARMAN Costa Da Oura Restaurant (Pty) Ltd t/a Umdloti Bush Tavern v Reddy 2003 4 SA 34 (SCA) - Frans Marx; Patrick Vrancken (Obiter, 2022)
On the evening of 31 October 1997, the respondent and his girlfriend visited the Umdloti Bush Tavern. A person by the name of Goldie was stationed behind the bar serving the customers. It appeared to the respondent that Goldie served everyone but him and his girlfriend. When another barman approached him, the respondent remarked that Goldie could take a few lessons regarding service from the second barman. Goldie heard this remark, became agitated and glared at the respondent. He further beckoned the respondent to come closer. The respondent reacted by saying words to the effect that he “did not come for people like that” (Costa Da Oura Restaurant (Pty) Ltd T/A Umdloti Bush Tavern v Reddy 2003 4 SA 34 (SCA) par 30). This further agitated Goldie and he occasionally stared at the respondent and appeared to be aggressive. When the respondent and his girlfriend were about to leave, the respondent generously tipped the barman who had served them. Goldie saw this and quickly exited the bar. When the respondent reached the corridor in the immediate vicinity of the bar, Goldie assaulted him, causing injuries which were reasonably serious. Immediately after the incident the manager of the Umdloti Bush Tavern summarily dismissed Goldie “because he had broken the rules that regulated how he should perform his basic duties” (par 41). The simple question to be decided was whether the appellant was vicariously liable under the circumstances. The crux of the respondent’s contentions was that the incident was sufficiently connected with the scope of employment of the appellant’s employee to establish vicarious liability, while the appellant contended that Goldie had acted for personal vengeance, on his own, against instructions and after he had abandoned his duties as a barman. The Durban and Coast Local Division in Reddy v Costa da Oura Restaurant (Pty) Ltd t/a Umdloti Bush Tavern (supra) found the appellant vicariously liable for damages resulting from the incident. On appeal the decision was reversed. The purpose of this discussion is to analyse the finding of the Supreme Court of Appeal and to ascertain whether the employer, in the circumstances of this case, should have been held liable. In the process of doing so, the background to the ruling will be explained and the legal policy implications of the decision assessed.